Análise espaço-temporal dos desastres naturais no município de Erechim - RS, no período de 1986 a 2011 - Peretti, Vanessa Aline (2013)
This research concerns in a survey of natural disasters that happened in the municipality of Erechim / RS between the years 1986 to 2011.The main objectives are: to identify and quantify the disasters happened in the city over the past 25 years; to identify the seasonal year in which they occurred and the type of event that caused the largest number of disasters; to identify and map the neighborhoods that were most affected; to investigate events according to the triggering source: meteorological, hydrological and climatologically. As well as to update the existing data on the subject matter. The literature survey was the first stage of this work. After the collection of data on episodes of natural disasters in the municipality of Erechim during the timescale of this research was conducted. It was done using the following sources: the files of the county Civil Defense, which comprise the decrees of Emergency and Public Calamity, the collection of records of the Fire Department of the municipality and the local newspaper circulation. Softwares were used for mapping and field work as well. They were essential to assess the situation locus of affected sites. At the end of this research it can be concluded that in the period from 1996 to 2011 sixty-five events causing disaster happened in Erechim-RS. The majority of them are of meteorological origin as gales and hail gales or climatological as droughts. Most of these events occurred in the spring and summer.